Species Diversity of Familia Poaceae in The Coal Mine Reclamation Area of PT Adaro Indonesia Tabalong - Riza Arisandi; Dharmono, Muchyar (Universitas Sebelas Maret, 2015)
Poaceae, one familia of plants with about 500 genera and 3,000 species, has the ability to spread rapidly by seed that is lightweight and easy carried by the wind,and is a pioneer plant. Reclamation is an effort to utilize, repair and improve less productive soil fertility through the application of technology.This research aimed to describe the species and the abundance of familia Poaceae found in the coal mine reclamation area of PT Adaro Indonesia Tabalong. This research was descriptive with observation technique. The method used was the 1 m x 1 m quadrant.The sampling technique performed on reclamation area of 9.7 ha by creating 100 sample points were divided into four observation stations, at each observation stations was created 25 sample points, with a distance of between sample points is 50 m. The sample is calculated based on the clump. Abundance calculated based on important value (NP) and diversity index (H') of the formula Shannon-Winner. Seventeen species of familia Poaceae were found.The highest abundance wasEleusine indica (L.) Gaertn. (NP = 46.87) and the lowest wasSaccharum spontaneum L. (NP = 2,20). Diversity of species familia Poaceae in the area (H') was 2,47.Keywords: Species diversity, Poaceae, reclamation